High‐Performance Large‐Scale Solar Steam Generation with Nanolayers of Reusable Biomimetic Nanoparticles. Issue 1 (9th January 2017) - Liu, Changxu; Huang, Jianfeng; Hsiung, Chia‐En; Tian, Yi; Wang, Jianjian; Han, Yu; Fratalocchi, Andrea
Abstract : The harvesting of solar radiation for steam generation has drawn wide attention as a future sustainable technology for the renewable production of clean water worldwide. Here, a new super‐dark metasurface of 200 nm thickness is presented, which reaches a solar thermal efficiency of 87% when exposed to an intensity of only 2.3 sun, maintaining a stable efficiency of 90% at higher solar intensities. The metasurface is composed of extremely robust nanoparticles, which are up to 98% recyclable and can be produced on massively large scales by wet chemistry. By employing such reusable nanoparticles on an area of 1 m 2, 1.2 kg of seawater can be purified within only 1 h under natural sunshine. With such excellent performances, this nanomaterial can open new applications of high‐performance solar steam. Abstract : Large‐scale solar steam generation with biomimetic ultradark nanoparticles is presented. Each nanoparticle is composed of a nanorod and a nanosphere attached together. When a 200 nm thick membrane of nanoparticles is illuminated by sunlight, it generates steam from water with an efficiency that is higher than any other material available today. Nanoparticles are fully recyclable and produced by wet‐chemistry techniques.